1971
DOI: 10.1104/pp.48.6.712
|View full text |Cite
|
Sign up to set email alerts
|

The Rate of Photorespiration during Photosynthesis and the Relationship of the Substrate of Light Respiration to the Products of Photosynthesis in Sunflower Leaves

Abstract: Single attached leaves of sunflower (Helianthus annus L."Mennonite") were supplied "CO2 of constant specific radioactivity in gas mixtures containing various CO2 and 02 concentrations. The "CO2 and C02 fluxes were measured concurrently in an open system using an ionization chamber and infrared gas analyzer.The rate of photorespiration (5.7 + 0.3 mg CO2-dm 2 hr-') during photosynthesis in 21% 02 at 25 C and 3,500 footcandles was over three times the rate of dark respiration and was independent of C02 concentrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

8
57
0
2

Year Published

1974
1974
2019
2019

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 139 publications
(67 citation statements)
references
References 30 publications
8
57
0
2
Order By: Relevance
“…In the absence of 02, the scheme indicates that net photosynthesis will increase by about 43(>. This expected increase is consistent with experimental observations (12,19 rate of change of P-glycolate concentration was zero, and the rates of glycolate accumulation and P-glycolate hydrolysis were determined from the solution of two simultaneous equations (3). In these calculations, it was assumed that the rate of P-glycolate hydrolysis was proportional to the P-glycolate concentration (i.e.…”
supporting
confidence: 79%
See 2 more Smart Citations
“…In the absence of 02, the scheme indicates that net photosynthesis will increase by about 43(>. This expected increase is consistent with experimental observations (12,19 rate of change of P-glycolate concentration was zero, and the rates of glycolate accumulation and P-glycolate hydrolysis were determined from the solution of two simultaneous equations (3). In these calculations, it was assumed that the rate of P-glycolate hydrolysis was proportional to the P-glycolate concentration (i.e.…”
supporting
confidence: 79%
“…C02) at 25 C. This scheme demonstrates that glycolate accumulation can equal 50%C of net carbon fixed in the presence of an inhibitor of glycolate oxidase, a-HPMS (a-hydroxypyridinemethanesulfonic acid), as observed by Zelitch (28), when RuDP carboxylase fixes one 02 molecule per four CO2 molecules. In the absence of a-HPMS, the scheme indicates that the rate of photorespiratory CO2 evolution equals about 14e1 the rate of photorespiratory CO2 evolution equals about 14%c the rate of net photosynthesis, in agreement with the direct measurements of Ludwig and Canvin (19). In the absence of 02, the scheme indicates that net photosynthesis will increase by about 43(>.…”
supporting
confidence: 75%
See 1 more Smart Citation
“…Such results provide a first approximation for the turnover rate of the alternative carbon source(s), i.e. on the order of 10 h. The partial labeling of isoprene emitted under CO 2 -free air is consistent with partial labeling of CO 2 respired into CO 2 -free air (Ludwig and Canvin, 1971). Although in principle, the unlabeled carbon source could result from refixation of the respired CO 2 , such refixation under CO 2 -free air is very small (Loreto et al, 1999).…”
Section: Characteristicsmentioning
confidence: 52%
“…But Hewitt et al (1990) showed that isoprene is not produced predominantly via photorespiration. It was previously suggested also that photorespiratory intermediates originate from short-term carbon storage, rapidly labeled by recent assimilation (Ludwig and Canvin, 1971;Loreto et al, 1999;Haupt-Herting et al, 2001). Such rapid labeling is inconsistent with the possibility that photorespiration is the source for unlabeled carbon in isoprene as observed here.…”
Section: Characteristicsmentioning
confidence: 99%